Microsoft PowerPoint best practices, tips, and techniques an indispensable guide to mastering PowerPoint's advanced tools to create engaging presentations - Bossé, Chantal (Packt Publishing, Limited, 2023)
Want to become a PowerPoint Pro? Written by a PowerPoint expert and Microsoft MVP, this book helps you create visually appealing PowerPoint presentations using advanced tools, features, and expert techniques for better impact Purchase of the print or Kindle book includes a free PDF eBook Key Features Learn how to plan your content and prepare your PowerPoint masters Create beautiful content using PowerPoint features and add-ins Deliver impressive presentations by leveraging PowerPoint's advanced delivery tools Book Description Giving great business presentations that stand out can mean the difference between getting and losing out on an important promotion, a critical client deal, or a grant. To start creating PowerPoint presentations that showcase your ideas in the best light possible, you'll need more than attractive templates; you'll need to leverage PowerPoint's full range of tools and features. This is where this PowerPoint book comes in, leading you through the steps that will help you plan, create, and deliver more impactful and professional-looking presentations. The book is designed in a way to take you through planning your content efficiently and confidently preparing PowerPoint masters. After you've gotten to grips with the basics, you'll find out how to create visually appealing content using the application's lesser known, more advanced features, including useful third-party add-ins. The concluding chapters will equip you with PowerPoint's advanced delivery tools, which will enable you to deliver memorable presentations. By the end of this book, you'll be able to confidently choose processes to create and deliver impactful presentations more efficiently. What you will learn Plan your PowerPoint presentation content and know your audience Prepare PowerPoint masters to speed up the development process and maintain consistency Add and modify visual and multimedia elements Use transitions and animations efficiently Build flexibility and interactivity into your presentations Practice your delivery with Presenter Coach Leverage Presenter View during delivery to increase your confidence Use PowerPoint Live in Teams for easy-to-manage remote presentations Who this book is for If you are a business professional looking for best practices for presentations and are interested in the features PowerPoint has to offer to help you create and deliver impactful presentations, this book is for you. No formal presentation design knowledge is needed, but you do need to know PowerPoint's basic tools and functions such as starting and saving files, adding, copying, pasting, or moving slides. A sound understanding of cloud storage and the use of Office 365 is also needed.